ATPase Inhibitory Factor 1 Promotes Hepatocellular Carcinoma Progression After Insufficient Radiofrequency Ablation, and Attenuates Cell Sensitivity to Sorafenib Therapy - Kong, Jian; Yao, Changyu; Ding, Xuemei; Dong, Shuying; Wu, Shilun; Sun, Wenbing; Zheng, Lemin (Frontiers in Oncology, 2020)
Epithelial-mesenchymal transition (EMT) and angiogenesis is involved in tumor progression after radiofrequency ablation (RFA). ATPase inhibitory factor 1 (IF1) is a bad predictor of prognosis. Sorafenib inhibited EMT of HCC after RFA. Whether IF1 promotes the EMT and angiogenesis of hepatocellular carcinoma (HCC) after insufficient RFA and attenuates the effect of sorafenib is investigated. In this study, higher expression of IF1 was found in residual tumor after insufficient RFA. Hep3B or Huh7 cells after insufficient RFA in vitro were designated as Hep3B-H or Huh7-H cells. Hep3B-H or Huh7-H cells exhibited enhanced capacities of colony formation, migration and increased expression of EMT associated markers and IF1 compared with Hep3B or Huh7 cells. IF1 knockdown in Hep3B-H or Huh7-H cells decreased the colony formation and migratory capacity, and IF1 overexpression in Hep3B or Huh7 cells increased these capacities. IF1 in HCC cells directly and indirectly affected angiogenesis of TAECs after insufficient RFA. IF1 promoted growth and metastasis of HCC cells after insufficient RFA in vivo. IF1 increased resistance of HCC cells after insufficient RFA to sorafenib in vitro and in vivo. Higher IF1 expression indicated poor disease survival in HCC patients after sorafenib therapy. NF-κB activation induced by IF1 attenuated the effect of sorafenib on HCC cells after insufficient RFA. Our results demonstrated that IF1 promotes the EMT and angiogenesis, and attenuates HCC cell sensitivity to sorafenib after insufficient RFA through NF-κB signaling.